Comparison of Three Different TTF-1 Clones in Resected Primary Lung Cancer and Epithelial Pulmonary Metastases. Issue 6 (30th August 2018) - Vidarsdottir, Halla; Tran, Lena; Nodin, Björn; Jirström, Karin; Planck, Maria; Mattsson, Johanna S M; Botling, Johan; Micke, Patrick; Jönsson, Per; Brunnström, Hans
Abstract: Objectives: Immunohistochemical staining against thyroid transcription factor 1 (TTF-1) is often used to distinguish lung adenocarcinoma from squamous cell carcinoma and pulmonary metastasis. Methods: TTF-1 expression was examined using the antibody clones 8G7G3/1, SPT24, and SP141 on tissue microarrays from 665 cases of resected lung cancers and 428 pulmonary metastases. Results: Most lung adenocarcinomas, 89%, 93%, and 93%, were positive with TTF-1 clones 8G7G3/1, SPT24, and SP141, respectively. The corresponding figures for lung squamous cell carcinomas were 0%, 6%, and 8%. In total, five (2%), 19 (7%), and 21 (8%) of the pulmonary metastases from colorectal adenocarcinomas were positive with clones 8G7G3/1, SPT24, and SP141, respectively. Other TTF-1–positive pulmonary metastases (n = 8) were thyroid, urothelial, pancreatic, small bowel, and cervix carcinomas. Conclusions: TTF-1 expression in lung cancer and pulmonary metastases differs between clones, with 8G7G3/1 being more specific but less sensitive compared with SPT24 and SP141.